(untitled) (Journal Of Educational and Psychological Researches, 2018)
The aim of this study to investigate the sexual harassment, prevention strategies, and the appropriate ways that tackle this phenomena. The current research consisted of four chapter; the first chapter gave a general introduction about the targeted topic followed by the problem of statement, the significance of study, study’s aims, and end with the limitations of study. The second section of chapter one referred to the common concepts of study. Third section addressed the previous studies that related to the current one. Chapter two concerned with the sexual violence against minors. It has four section; first section addressed number of concepts which related to sexual violence. The second section focused on the implications of sexual violence and harassment. Third section presented the prospective of sociology toward sexual violence and harassment (family disintegration, breaking up and the post-trauma disorders, violence against minors, child trafficking as one of the serious challenges during childhood, and the effect of sexual violence and harassment on society). The third chapter revealed the Islamic law’s prospective of sexual anomalies and sexual violence, How parents prevent minors from sexual violence, the role of parents when the harassment occurs, how to promote the protective and preventive measures, the using of appropriate techniques to prevent minors against sexual violence, united nation’ rules of sexual violence, united nation’s role of making ultimate strategies of sexual violence, and finally, he put forward some recommendations and suggestions.